Electrodeposition of Zinc from Zinc Oxide in 2:1 Urea/1-Butyl-3-methylimidazolium Chloride Ionic Liquid. Issue 9 (2nd August 2017) - Liu, Aimin; Shi, Zhongning; Reddy, Ramana G.
Abstract : In this study, zinc oxide (ZnO) was dissolved in 2:1 mole ratio of urea/1-butyl-3-methylimidazolium chloride (urea-BMIC) ionic liquids and electrochemically reduced to metallic zinc (Zn) on the cathode. The electrochemical behavior of zinc species in the urea-BMIC-ZnO ionic liquids was investigated by cyclic voltammetry, chronopotentiometry, and chronoamperometry techniques at 373 K using a tungsten working electrode and silver reference electrode. The cyclic voltammograms and chronopotentiograms indicate that the reduction of zinc species to metallic Zn is a diffusion-controlled quasi-reversible process and it proceeds via an apparent two-electron transfer process on tungsten working electrode. From the chronoamperometric analysis, zinc deposition in urea-BMIC involves in a three-dimensional instantaneous nucleation and diffusion-controlled growth at 373 K. The value of diffusion coefficient of zinc species in the urea-BMIC (molar ratio 2:1) ionic liquids at 373 K is 4.39 × 10 −9 cm 2 ·s −1 . Zinc coatings were prepared on copper substrates at various current densities (constant current electrolysis) and different cathodic potentials (constant potential electrolysis). SEM micrograph indicated that a uniform, dense, and compact coating was produced by potentiostatic electrolysis at −1.1 V (vs. Ag). In addition, the obtained electrodeposit on the Cu substrate was metallic Zn as confirmed by XRD pattern and EDS spectrum. The optimized current efficiency (99.24%) and energy consumption (3.29 kWh/kg) was obtained by potentiostatic electrolysis at −1.1 V (vs. Ag) and 383 K in urea-BMIC ionic liquids containing 0.49 mmol/mL ZnO.